Calcium and Potassium Foliar Sprays Affect Fruit Skin Color, Quality Attributes, and Mineral Nutrient Concentrations of 'Red Delicious' Apples. Issue 4 (2nd October 2017) - Solhjoo, S.; Gharaghani, A.; Fallahi, E.
ABSTRACT: This study was conducted to evaluate the influences of foliar spray of potassium (K), calcium (Ca), and their combination on the fruit red skin color and quality attributes of 'Red Delicious' apple under conditions of south central Iran with warm and dry summer, where low and high temperature differences are low. The trees were sprayed five times using 5 g L –1 calcium chloride (CaCl2 ) at 3-week intervals starting from 3 weeks after full bloom and three times (at 9, 12, and 15 weeks after full bloom) using 2.5 g L –1 K sources [potassium chloride (KCl), potassium sulfate (K2 SO4 ), and potassium nitrate (KNO3 )] during two growing seasons in 2013 and 2014. Anthocyanin, some physicochemical attributes, and fruit mineral concentrations were measured at harvest. Results showed that spraying with K, CaCl2, and their combinations significantly increased fruit weight, sugar and anthocyanin concentrations, firmness, and K uptake. A combined foliar application of CaCl2 and each of the K sources was more effective on the improvement of fruit color, firmness, fruit K and Ca uptake, and K/Ca ratio as compared to the case when either K or Ca was applied alone.